1992
DOI: 10.1063/1.461893
|View full text |Cite
|
Sign up to set email alerts
|

Model surface studies of metal oxides: Adsorption of water and methanol on ultrathin MgO films on Mo(100)

Abstract: Adsorption and reaction of formic acid on NiO(100) films on Mo(100): Temperature programmed desorption and high resolution electron energy loss spectroscopy studies J. Chem. Phys. 97, 9447 (1992); 10.1063/1.463268 CO interaction with ultrathin MgO films on a Mo(100) surface studied by infrared reflection-absorption spectroscopy, temperature programmed desorption, and xray photoelectron spectroscopy Model surface studies of magnesium oxide have been carried out using surface sensitive techniques. Ultrathin MgO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 27 publications
8
67
0
Order By: Relevance
“…[61] The difference between the calculated and experimental frequency data indicates that the coadsorption water under experimental measurement conditions may reduce the bond strength of OH species.…”
mentioning
confidence: 98%
“…[61] The difference between the calculated and experimental frequency data indicates that the coadsorption water under experimental measurement conditions may reduce the bond strength of OH species.…”
mentioning
confidence: 98%
“…One such important metal oxide is magnesium oxide (MgO). Both experimental tools (Coluccia et al 1987;Knozinger et al 1993;Peng and Barteau 1991;Wu et al 1992;Zhou and Cowin 1996) and theoretical tools (Deleeuw et al 1995;Langel and Parrinello 1994;Refson et al 1995;Scamehorn et al 1993) have been used to investigate the water/MgO interface. McCarthy et al (1996) parameterized a two-body force field to describe solid-water interactions based on prior ab initio correlation-corrected periodic Hartree-Fock theoretical results (Scamehorn et al 1993(Scamehorn et al , 1994.…”
Section: Other Simulated Systemsmentioning
confidence: 99%
“…5 MgO films are among the most studied systems since, due to their relatively simple electronic and atomic structure, they were assumed as a model for investigating metal-oxide interface properties. 6 Ag(100) is an optimal substrate for the film deposition, since the small mismatch between the Ag and the MgO lattice constants allows for epitaxial growth, as demonstrated recently by scanning tunneling microscopy (STM). 7,8 Such experiments, aimed at clarifying the structure of MgO layers in the very early stages of film growth, showed that initially both MgO islands and pyramidal structures form on the Ag(100) surface.…”
Section: Introductionmentioning
confidence: 99%